PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK SEKOLAH DASAR - Masyitah, Ayu; Gusmiva, Adelsa; Efendi Hutagalung, Erwin; Muhammadin Al Fath, Ayatullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical communication skills are a fundamental aspect of mathematics learning; however, in reality, elementary school students’ proficiency in this area remains relatively low due to teaching approaches that are still teacher-centered. This study aims to conduct an in-depth analysis of the impact of the Realistic Mathematics Education (RME) approach on the mathematical communication skills of elementary school students based on the findings of previous research. The research methodology employed was a literature review, examining 10 scientific articles indexed in SINTA 1–4 and Scopus from 2020 to 2026. Data analysis was conducted using qualitative descriptive methods through a series of stages involving organization, grouping, comparison, and synthesis of findings. The research results indicate that the RME approach consistently yields a significant positive impact on improving students’ mathematical communication skills. This improvement is evident in students’ ability to convey ideas, use mathematical representations, and connect concepts to real-life contexts. However, several variables influence RME performance; students with moderate to high initial cognitive abilities achieve greater improvement. Furthermore, the success of RME heavily depends on collaborative activities and adequate learning media support, such as RME-based e-modules or worksheets. In conclusion, RME is an effective strategy for improving mathematical communication, but its implementation must be tailored to student characteristics and supported by relevant media.